A Pilot Open Trial of Brief Psychodynamic Psychotherapy for Panic Disorder - Milrod, Barbara (American Psychiatric Press, Inc, 2001)
This is a complete report of an open trial of manualized psychodynamic psychotherapy for treatment of panic disorder, Panic-Focused Psychodynamic Psychotherapy (PFPP). Twenty-one patients with PD were entered into a trial of twice-weekly, 24-session treatment. Sixteen of 21 experienced remission of panic and agoraphobia. Treatment completers with depression also experienced remission of depression. Improvements in symptoms and in quality of life were substantial and consistent across all measured areas. Symptomatic gains were maintained over 6 months. This report was prepared specifically to describe 6-month follow-up on these patients. Psychodynamic psychotherapy appears to be a promising nonpharmacological treatment for panic disorder.